Effectiveness of stannous fluoride in treating gingivitis: a literature review - Alhossan, Abdulaziz; Alsomali, Raed; Alanazi, Abdulkarim; Alotaibi, Naif (International Journal Of Community Medicine And Public Health, 2024)
The purpose of the study was to investigate and evaluate the existing research studies on stannous fluoride (SnF2) dentifrices to answer the question of whether they are effective in enhancing oral health and reducing gingival inflammation. The study utilized a systematic approach, including a comprehensive literature search for relevant randomized controlled trials (RCT) and cohort studies. Inclusion criteria focused on SnF2 dentifrices’ effects on periodontal health in individuals with gingivitis. The reviewed studies consistently demonstrated that dentifrices containing SnF2 were more effective than both negative and positive controls in improving periodontal health. The findings support the potential of SnF2 dentifrices as a promising option for enhancing oral health and reducing gingival inflammation. Further well-designed randomized trials are needed to strengthen the evidence base and provide comprehensive support for the efficacy of SnF2 dentifrices in improving oral health.